Meningkatkan Motivasi Wirausaha Masyarakat Di Sekitar Aliran Sungai Cikapundung, Kelurahan Balonggede - Yayandi, Muhamad; Susilawati, Enung; Zein, Ratu Marsya Chaerunissa; Yusnaini, Yusnaini; Juliartha, Evie Farida; Handayani, Sri; Ensa, Hasyafira; Darusatul, Maudi; Kirana, Chandra; Nurlaila, Nurlaila; Nurazizah, Siti; Alawi, Muhammad Ridwan; Ikhsan, M; Salsabillah, Soraya; Hanifah, Siti Nur (Journal Of Human And Education (JAHE), 2025)
Abstract Entrepreneurial motivation is a key factor in improving the economic well-being of communities, especially for those living around the Cipakundung River, Balonggede Village. The low level of entrepreneurship in this area is caused by various obstacles, including limited capital, lack of skills, and minimal understanding of environmentally-based business opportunities. Therefore, this study aims to enhance the motivation and entrepreneurial skills of the community through socialization programs, training, and business mentoring based on an educational and community empowerment approach. The method used in this study involved a participatory approach with stages of socialization and problem identification, entrepreneurship training, business mentoring, as well as monitoring and evaluation. This program was implemented for 50 participants from various community groups living around the Cipakundung River. The results showed a significant increase in public awareness and interest in entrepreneurship, as well as improved skills in business planning and marketing strategies. Additionally, this program successfully encouraged the formation of new business groups that utilize local resources, such as waste processing into economically valuable products. In conclusion, an educational and community-based approach has proven effective in increasing motivation and sustaining community businesses, although continuous support in the form of capital access and market network strengthening is still needed to further optimize the developed enterprises. Keywords: Entrepreneurial Motivation, Community Empowerment, Environmentally-Based Entrepreneurship